How does Parelli measure up? (poster) - North, Steve; Hemingway, Ann; McLean, Andrew; Laurie, Harriet; Ellis-Hill, Caroline (International Society for Equitation Science, 2016)
Poster presented at 12th International Society for Equitation Science Conference (ISES2016) to accompany: Steve North, Ann Hemingway, Andrew McLean, Harriet Laurie and Caroline Ellis-Hill. 2016. Evaluating a natural horsemanship program in relation to the ISES first principles of horse training. In proceedings of The 12th International Society for Equitation Science Conference (ISES2016). June 23-25. IFCE (Institut Français du Cheval et de L’équitation), Saumur, France.DOI: 10.5281/zenodo.54733. http://dx.doi.org/10.5281/zenodo.54733